Relationship of biological maturation with muscle power in young female athletes - de Almeida-Neto, P. F.; Bulhões-Correia, A.; de Matos, D.; de Alcântara Varela, P. W.; Monteiro Pinto, V. C.; Dantas, P. M.; Aidar, F.; de Araujo Tinoco Cabral, B. G. (International Journal of Exercise Science, 2021)
There is still no consensus on how biological maturation (BM) affects the muscle power of upper and lower limbs in young people. The objective was to verify associations between BM and muscle power, as well as to compare the muscle power of upper (ULP) and lower limbs (LLP) among young athletes in different stages of BM. The sample consisted of 79 female athletes (10.9 ± 1.11 years old). Regarding BM, the sample was divided into three groups: delayed BM, synchronized BM, and accelerated BM. BM was identified by subtracting chronological age from bone age (BA). BA was measured by a mathematical model based on anthropometry. The muscular power of the upper limbs was analyzed by the medicine ball launch test, and that of the lower limbs was analyzed by the countermovement jump on a force platform. BM and BA correlated with ULP (BA: r =0.74; BM: r =0.65) and LLP (BA: r = 0.50; BM: r =0.41). In the comparisons of the tests of ULP and LLP, the groups with synchronized and accelerated BM were superior to the group with delayed BM. The advance of BM is associated with the ULP and LLP, as well as the advance of the BM affects muscle power in young female athletes. This occurs due to the increase in body mass resulting from the advancement of BM, which may favor the predominance of lean body mass, assisting in the production of muscle strength.